Online Apologies in Japanese - Diegoli, Eugenia, (Language and Linguistics E-Books Online, Collection 2025., 2025)
Apologies are ubiquitous in contemporary societies, yet their meanings and functions are rarely straightforward. Online Apologies in Japanese provides a comprehensive account of how three Japanese expressions commonly considered apologetic ( gomen, su(m)imasen and mōshiwake arimasen ) work in a data set collected from the Q&A website Yahoo! Chiebukuro. The focus is on three variables: their pragmatic functions, the discursive strategies they co-occur with, and the events and behaviours that warrant them. Theoretically, this book introduces a combination of established and emerging approaches in the field of pragmatics. Methodologically, it brings together corpus linguistics and discourse analysis for the study of Japanese. En route, it contains numerous insights on the speech act of apology, (im)politeness and related areas in a non-Western context.